When COVID-19 strikes mental health: a measurement analysis of reassurance seeking behavior scale in Peruvian population - Manrique-Millones, Denisse; García-Serna, Jackeline; Castillo-Blanco, Ronald; Fernández-Ríos, Nataly; Lizarzaburu-Aguinaga, Danny Alonso; Parihuamán-Quinde, Geraldina Rebeca; Villarreal-Zegarra, David (Frontiers in Psychology, 2023)
Background: The long-lasting impact of the COVID-19 pandemic cannot be overstated. To combat its dire consequences, some screening measures have been hastily developed and require robust verification to explore their adequacy across different groups The present research study aimed to analyze measurement invariance by sociodemographic characteristics of the Coronavirus Reassurance Seeking Behavior Scale (CRSB) in Peruvian adults. Methods: 661 participants completed The Coronavirus Reassurance Seeking Behavior Scale (CRSB), the Coronavirus Anxiety Scale (CAS), and sociodemographic information a subgroup filled in the Patient Health Questionnaire (PHQ-9). Reliability and measurement invariance across sociodemographic characteristics were analyzed. Likewise, associations with depression and dysfunctional coronavirus anxiety were examined. Results: Results showed that the single factor structure of the CRSB with correlated errors fitted the data adequately and the instrument was invariant across gender, age and loss of a significant relative to COVID-19. In addition, significant associations with depressive symptoms and dysfunctional anxiety were found. Conclusions: The findings of the present study suggest that the Coronavirus Reassurance Seeking Behaviors Scale is invariant across different sociodemographic characteristics.